Prices and profits in cotton textiles during the Industrial revolution - Harley, C (University of Oxford, 2010)
Cotton textile firms led the development of machinery-based industrialization in the Industrial Revolution. This paper presents price and profits data extracted from the accounting records of three cotton firms between the 1770s and the 1820s. The course of prices and profits in cotton textiles illumine the nature of the economic processes at work. Some historians have seen the Industrial Revolution as a Schumpeterian process in which discontinuous technological change created large profits for innovators and succeeding decades were characterized by slow diffusion. Technological secrecy and imperfect capital markets limited expansion of use of the new technology and output expanded as profits were reinvested until eventually the new technology dominated. The evidence here supports a more equilibrium view which the industry expanded rapidly and prices fell in response to technological change. Price and profit evidence indicates that expansion of the industry had led to dramatic price declines by the 1780s and there is no evidence of super profits thereafter.